(E)-1-[4-(Hexyloxy)phenyl]-3-(4-hydroxyphenyl)prop-2-en-1-one - Hasnain, Hussain; Zainab, Ngaini; Siti Muhaini, Haris Fadzillah; Ibrahim, Abdul Razak; Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title compound, C21H24O3, intermolecular O—HO and C—HO interactions form bifurcated acceptor bonds, generating R2 1 (6) ring motifs. These ring motifs link the molecules into extended chains along [010]. The crystal structure is further stabilized by C—H interactions.